Implikasi Hukum Kesehatan terhadap Kasus Keracunan Makanan dalam Program Makan Bergizi Gratis di Indonesia - Arif Susanto (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The Free Nutritious Meal Program (MBG), launched by the Indonesian government in 2025 to improve children's nutrition, has led to serious legal and health issues following thousands of food poisoning cases. This study explores legal health responsibilities, accountable parties, law enforcement mechanisms, and preventive measures. Using normative and empirical juridical approaches with qualitative analysis, the findings reveal violations of health and food safety rights, subject to criminal, civil, and administrative sanctions. Regulatory reform is essential to ensure the safe and responsible continuation of the MBG program.